THE EFFECT OF COMPANY SIZE, NET PROFIT MARGIN, CURRENT RATIO, DEBT TO EQUITY RATIO, BI RATE ON THE PROFIT GROWTH ON PROPERTY & REAL ESTATE COMPANIES LISTED ON IDX 2019-2023 - Antony, Aislinn; Sihombing, Sagita Charolina; Sihombing, Dina Agnesia (Kurs : Jurnal Akuntansi, Kewirausahaan dan Bisnis, 2025)
This research purposed to determine the effect of company size, net profit margin, liquidity ratio, leverage, and inventory turnover on profit growth in property and real estate companies listed on the IDX for the period 2019-2023. This study uses secondary data. The sampling technique in this study uses purposive sampling. The number of samples obtained were 42 companies. The analysis method of this research uses descriptive analysis and several types of evaluation usedf SmartPLS4 software. From this research, it can be concluded that only BI Rate has a significant effect on profit growth. Meanwhile, the proportion of company size, net profit margin, current ratio and debt to equity ratio have no significant effect on on profit growth Penelitian ini bertujuan untuk mengetahui pengaruh ukuran perusahaan, net profit margin, current ratio, debt to equity ratio dan suku bunga BI terhadap pertumbuhan laba pada perusahaan properti dan real estat yang terdaftar di BEI periode 2019-2023. Penelitian ini menggunakan data sekunder. Teknik sampel pada penelitian ini menggunakan purposive sampling. Jumlah sampel yang diperoleh sebanyak 42 perusahaan. Metode analisis penelitian ini menggunakan analisis deskriptif serta beberapa jenis evaluasi dengan menggunakan bantuan software SmartPLS4. Dari penelitian ini diperoleh kesimpulan bahwa hanya suku bunga BI yang memiliki pengaruh signifikan terhadap pertumbuhan laba. Sedangkan ukuran perusahaan, net profit margin, current ratio dan debt to equity ratio tidak memiliki pengaruh yang signifikan terhadap pertumbuhan laba.